Chapter Aspectual pair, aspectual triplet, aspectual cluster: what is the unit of the category of aspect and can the answer be tested experimentally? - Samedova-Hajiyeva, Nezrin (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
This paper is an attempt to show that the problem of identifying the unit of the category of Russian aspect indicates the explanatory and predictive potential of an aspectological theory. We introduce a wider scientific community to the theory that regards the aspectual pair (or the two-term / binary paradigm) as the only one unit of the category of Russian aspect and that characterizes the notion of the aspectual triplet as an obstacle to aspectological studies. We show how the theory explains Maslov’s (2004) paradox about so-called instantaneous / momentary / punctual verbs such as прыгнуть ‘to jump’. The advanced explanation can be tested by cognitive experiments, which will serve as one more argument for the aspectological theory that rejects the notion of aspectual cluster of any type.